2022
DOI: 10.3390/plants11202686
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Potential of Different Organs of Mistletoe (Viscum album L.) Collected from Various Host Tree Species in an Urban Area

Abstract: From an economic and ecological standpoint, it is crucial to investigate the biologically active compounds of mistletoe plants, which are currently discarded by pruning urban mistletoe-infested trees. In the present study, the content of phenolic compounds, triterpenic and organic acids, as well as the antioxidant activity of the extracts of various mistletoe organs (leaves, stems, and fruits) collected from the most infested tree species were investigated. The mistletoe samples collected from Betula pendula, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The antioxidant activity of G. maritima and S. marina extracts was determined by the ability to capture the radicals 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2 -azino-bis (3ethylbenzthiazolino-6-sulfonic acid (ABTS) and by the reducing ability when reacting with Fe(III) -2,4,6-tripyridyl-s-triazine complex (FRAP) according to [44]. Antioxidant activity by DPPH, ABTS, and FRAP was determined spectrometrically using a microplate reader (CLARIOstar, BMG Labtech, Germany).…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%
“…The antioxidant activity of G. maritima and S. marina extracts was determined by the ability to capture the radicals 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2 -azino-bis (3ethylbenzthiazolino-6-sulfonic acid (ABTS) and by the reducing ability when reacting with Fe(III) -2,4,6-tripyridyl-s-triazine complex (FRAP) according to [44]. Antioxidant activity by DPPH, ABTS, and FRAP was determined spectrometrically using a microplate reader (CLARIOstar, BMG Labtech, Germany).…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%
“…The amount of TPC in VA methanol extracts ranged from 9.81 to 22.76 mg GAE/g. It was determined that the amount of phenolic in the fruit extracts was higher than the branch and leaf extracts.Similarly, Skrypnik et al (2022) reported that TPC in mistletoe fruits was 3.0–3.2 times higher than in leaves and stems [55] …”
Section: Resultsmentioning
confidence: 91%
“…It was determined that the amount of ChemistrySelect phenolic in the fruit extracts was higher than the branch and leaf extracts.Similarly, Skrypnik et al (2022) reported that TPC in mistletoe fruits was 3.0-3.2 times higher than in leaves and stems. [55] The highest TPC was found in samples collected from Pyrus communis (22.76 mg GAE/g sample) at VA fruit methanol extracts. This was followed by Mespilus germanica (22.19 mg GAE/gfruit sample).…”
Section: Total Phenolic and Total Flavonoid Content Quantification An...mentioning
confidence: 90%
“…The mismatch of the IR spectrum reaches up to 40% and this was often found in studies using plants as objects of study. 41,42 Analysis of proton ( 1 H) and carbon ( 13 C) NMR of standard and analytes was performed using a 99.9% (w/v; 0.36 M) solution standard of quercetin and analytes dissolved in methanol-d 4 were acquired using the JEOL JNM ECS-400 NMR spectrometer (Figure 5). This spectrum reveals three types of proton and carbon signals as follows: aromatic protons carbon and hydroxy protons carbon of the analyte and standard, and solvent proton carbon.…”
Section: Discussionmentioning
confidence: 99%